Real time calorimetric characterisation of clay - drug complex dispersions and particles - A.M. Totea; I. Dorin; G. Gavrilov; P.R. Laity; B.R. Conway; L. Waters; K. Asare-Addo (Elsevier, 2019)
Isothermal titration calorimetry (ITC) along with attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX) and high-performance liquid chromatography (HPLC) were employed to investigate the process of adsorption of propranolol hydrochloride (PPN) onto magnesium aluminium silicate (MAS) and to characterise the MAS-PPN particles formed upon complexation. The composition of MAS was confirmed by infrared (IR) spectroscopy and a calcimeter. The calorimetric results confirmed the binding between PPN and MAS at various pHs and temperatures. The overall change in enthalpy was found to be exothermic with a comparatively small entropic contribution to the total change in Gibbs free energy. These findings suggest that the binding process was enthalpically driven and entropically unfavourable (lower affinity) suggesting hydrogen bonding and electrostatic interactions dominating the interaction. The variation of pH and temperature did not have a great impact on the thermodynamics of the binding process, as observed from the similarity in enthalpy (ΔH), entropy (ΔS) or Gibbs free energy (ΔG). A slight reduction in the binding affinity (Ka) with varing pH and temperature was however observed. SEM/EDX studies showed the occurrence of changes in the microstructural properties of MAS following complexation which may explain the potential of MAS-PPN complexes for controlled drug release promoting pharmaceutical innovation. Keywords: Magnesium aluminium silicate, Propranolol hydrochloride, Isothermal titration calorimetry, Complexation